Fatty Acid Composition of Opuntia Ficus-Indica Seed Oil Control Angiogenic Activity in Colon Carcinoma Cell Lines - Becer, Eda; Kabadayı, Hilal; Meriçli, Ali Hikmet; Kıvançlı, Barış; Vatansever, H. Seda; Meriçli, Filiz (Progress in Nutrition, 2021)
Opuntia ficus-indica belongs to the family Cactaceae that particularly rich in unsaturated fatty acids. The aim of this study was to investigate the composition and in vitro anti-angiogenic activity of spiny and thornless Opuntia ficus-indica seed (CPS) oils. Spiny and thornless CPS oils were obtained by supercritical CO2 extraction and analyzed by GC-MS. Cell growth and cytotoxicity were measured with MTT assay with different concentrations of spiny and thornless CPS oils in Colo-320 and Colo-741 cell lines. Anti-angiogenic activity of CPS oils were investigated by immunocytochemistry using antibodies directed against to Flt-1, Flk-1, eNOS, iNOS, IL-6, PGE2, TNF-α and VEGF. Oleic acid (17.6%; 15.6%), linoleic acid (55.9%; 60.1%), palmitic acid (12.4%; 12.3%), elaidic acid (4%; 4.1%) were determined as the major compounds of spiny and thornless CPS oils, respectively. In the MTT assay, 1:16 dilution spiny CPS oil was found to be active against Colo-320 and Colo-741 cells for 48h incubation. Also, 1:8 and 1:16 dilutions of thornless CPS oil were more effective at inhibiting Colo-320 and Colo-741 for 48 h, respectively.We conclude that spiny CPS oil decreased signaling molecules which play in PGE2 mediated and VEGF-dependent angiogenesis. Interestingly, thornless CPS oil increased angiogenesis thought signaling molecules in colon cancer cells.